1990
DOI: 10.1038/343767a0
|View full text |Cite
|
Sign up to set email alerts
|

A serine protease triad forms the catalytic centre of a triacylglycerol lipase

Abstract: True lipases attach triacylglycerols and act at an oil-water interface; they constitute a ubiquitous group of enzymes catalysing a wide variety of reactions, many with industrial potential. But so far the three-dimensional structure has not been reported for any lipase. Here we report the X-ray structure of the Mucor miehei triglyceride lipase and describe the atomic model obtained at 3.1 A resolution and refined to 1.9 A resolution. It reveals a Ser..His..Asp trypsin-like catalytic triad with an active serine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
560
2
29

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,187 publications
(612 citation statements)
references
References 20 publications
17
560
2
29
Order By: Relevance
“…The "open state" conformation would render the active site with a deformed structure more susceptible to the external environment, attributed to the loss of the shield provided by the lid in the "close state". 9 In brief, the above discussion clarifies a correlation between the support hydrophobicity and the thermal stability of the immobilized PCL. The support with MHM is preferable for an improvement in PCL thermal stability.…”
Section: Resultsmentioning
confidence: 90%
“…The "open state" conformation would render the active site with a deformed structure more susceptible to the external environment, attributed to the loss of the shield provided by the lid in the "close state". 9 In brief, the above discussion clarifies a correlation between the support hydrophobicity and the thermal stability of the immobilized PCL. The support with MHM is preferable for an improvement in PCL thermal stability.…”
Section: Resultsmentioning
confidence: 90%
“…No active enzyme was thought to occur in solution. Recent X-ray structure analyses of native and inhibitor -complexed Rhizomucor miehi lipase have revealed that a short peptide segment covering the active site in the absence of the substrate move in complexed enzyme so that the active site is exposed to the solvent [45,46]. Concomitantly the hydrophobicity of the surface area around the active site increases, which should contribute to the strong binding of the enzyme to the interface.…”
Section: Characterization Of Lipase From Aspergillus Niger Nrrl3mentioning
confidence: 99%
“…The same results were obtained with respect to Mucor miehei lipase. 14 ) Ester bonds of long and middle chain fatty acids (C s " CIS) were hydrolyzed by the lipase but the ester bond of a short chain fatty acid (C 4 ) resisted cleavage by the enzyme's lipolysis (Fig. 3).…”
Section: Enzymic Properties Of Lipasementioning
confidence: 99%